Legal Design as an effective tool for legal documents: the case of Environmental Criminal Law (Brazilian Journal of Police Sciences, 2022)
This article aimed to analyze the effectiveness of using Legal Design for the preparation of legal documents. For this, we used the methodology of qualitative literature review, of a basic nature. As main results it was found that Legal Design is a methodology used to improve the user experience with the legal system, seeking to make the user the center of this system, for that, Legal Design uses techniques to assist the user in their journey, enabling them to understand the message that the legal document seeks to convey, a message that is currently far-fetched by a forensic language that makes it difficult for lay users to understand. In this way, Legal Design has the power to transform the user's experience with the legal system, being effective when used in legal documents by providing the user, through understanding, with greater autonomy, allowing him to carry out his decision making.
Keywords: Legal Design; mining bonds; user; autonomy; forensic language